Non-Ulcer dyspepsia relation with environmental factors - A study in Sub Himalayas, India (Faculty of Medicine Universitas Indonesia, 2005)
Non ulcer dyspepsia is a common gastrointestinal problem, the etiopathogenesis of which is not well established. This study was planned to see the effect of environmental factors like smoking, tea, alcohol, and NSAIDs consumption with non-ulcer dyspepsia. This study was conducted in the department of Gastroenterology, Medicine and Radiology of I.G. Medical College, Shimla, India. Three hundred patients of non-ulcer dyspepsia were included in the study. Each case was matched with community control of same age and sex. A detailed history of smoking, tea, alcohol, and NSAIDs consumption was taken from the patients and controls. Consumption of tea as an environmental factor was found to be statistically significant in non-ulcer dyspepsia patients as compared to controls using multivariate regression. In the present study, environmental factors like smoking, alcohol, NSAIDs consumption did not show positive co-relation with non-ulcer dyspepsia. (Med J Indones 2005; 14: 50-4) Keywords: smoking, alcohol, tea, Non-steroidal anti-inflammatory drugs (NSAIDs)